2021
DOI: 10.1212/cpj.0000000000000964
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Streptococcal Brain Abscesses in a Patient Taking Secukinumab

Abstract: The approval of the IL-17A inhibitor Secukinumab (Cosentyx; Novartis International, King of Prussia, Pennsylvania) was a major advance in psoriasis treatment, with most patients experiencing a 75% reduction in severity1. Known side effects include an increase in minor infections, but no major infectious adverse events and no nervous system involvement1–4, leading to broad use and an increase in clinical trials targeting the IL-17 pathway. Here, we describe a patient on Secukinumab who presented with severe neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This disease needs to be treated promptly to avoid serious consequences. In 2021, Anjali et al [16] reported that brain abscesses appeared as high signal on DWI. The pus cavity of a brain abscess contains a viscous fluid consisting of a large number of inflammatory cells, necrotic tissue, bacteria, protein secretions, and other substances, which brings about a high viscosity inside the pus cavity.…”
Section: The Application Of Dwi In the Diagnosis Of Brain Diseasesmentioning
confidence: 99%
“…This disease needs to be treated promptly to avoid serious consequences. In 2021, Anjali et al [16] reported that brain abscesses appeared as high signal on DWI. The pus cavity of a brain abscess contains a viscous fluid consisting of a large number of inflammatory cells, necrotic tissue, bacteria, protein secretions, and other substances, which brings about a high viscosity inside the pus cavity.…”
Section: The Application Of Dwi In the Diagnosis Of Brain Diseasesmentioning
confidence: 99%